Answer:
Option A.
![y = (1)/(4) e^(-2t) + (5)/(8) e^(4t) - 2 t + (1)/(8)](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/zf4fl35pijgc7gwwj17nx344ln275nwdl5.png)
Step-by-step explanation:
This is a second order DE, so we'll need to integrate twice, applying initial conditions as we go. At a couple points, we'll need to apply u-substitution.
Round 1:
To solve the differential equation, write it as differentials, move the differential, and integrate both sides:
![y''=e^(-2t)+10e^(4t)](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/lb462ochq4xy2kyy0uxm1azt4i1eeqc6ji.png)
![(dy')/(dt)=e^(-2t)+10e^(4t)](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/srgo0v22ibpqlq61uhwvlcqqed8fs0qs6l.png)
![dy'=[e^(-2t)+10e^(4t)]dt](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/npa91rnf78ghlhykgapxapjhofujeguf59.png)
![\int dy'=\int [e^(-2t)+10e^(4t)]dt](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/gx41qoaqyor7utcejzvgi5qnwb3kqwa2oz.png)
Applying various properties of integration:
![\int dy'=\int e^(-2t) dt + \int 10e^(4t)dt\\\int dy'=\int e^(-2t) dt + 10\int e^(4t)dt](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/lkwzjwxz3m79bhasg5y9tvs8lpwsqcubmh.png)
Prepare for integration by u-substitution
, letting
and
![u_2=4t](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/ax2y8jwyr78mz0xyseohtkj4col6u5qxz0.png)
Find dt in terms of
![u_1 \text{ and } u_2](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/s2oqobscxklrm1kxo2vsb8crk2iigeaauc.png)
![u_2=4t\\du_2=4dt\\(1)/(4)du_2=dt](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/xytdy4j6f00en9a5r56aatbv5xkwlxoh2v.png)
![\int dy'=\int e^(u_1) dt + 10\int e^(u_2)dt\\\int dy'=\int e^(u_1) (-(1)/(2) du_1) + 10\int e^(u_2) ((1)/(4) du_2)\\\int dy'=-(1)/(2) \int e^(u_1) (du_1) + 10 *(1)/(4) \int e^(u_2) (du_2)](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/jlwvglzmryjhhvje5e3g8fnj4v5z2e0vtu.png)
Using the Exponential rule (don't forget your constant of integration):
![y'=-(1)/(2) e^(u_1) + 10 *(1)/(4)e^(u_2) +C_1](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/cztfaf7yyytiyuj47erhb0adhri14qe8ou.png)
Back substituting for
:
![y'=-(1)/(2) e^((-2t)) + 10 *(1)/(4)e^((4t)) +C_1\\y'=-(1)/(2) e^(-2t) + (5)/(2)e^(4t) +C_1\\](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/fgwerutyslh1jb5uhvunz2wux66lsdtkdy.png)
Finding the constant of integration
Given initial condition
![y'(0)=0](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/enr1vkzht1e8bu8gbzjfyf08mmjkjs0g8u.png)
![y'(t)=-(1)/(2) e^(-2t) + (5)/(2)e^(4t) +C_1\\0=y'(0)=-(1)/(2) e^(-2(0)) + (5)/(2)e^(4(0)) +C_1\\0=-(1)/(2) (1) + (5)/(2)(1) +C_1\\-2=C_1\\](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/fuxncs87u9zqfitvs0cbx5vv4n1d4c43xd.png)
The first derivative with the initial condition applied:
![y'(t)=-(1)/(2) e^(-2t) + (5)/(2)e^(4t) -2\\](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/o8gswas92lo4irr5lrsnha1tpggv8ln734.png)
Round 2:
Integrate again:
![y' =-(1)/(2) e^(-2t) + (5)/(2)e^(4t) -2\\(dy)/(dt) =-(1)/(2) e^(-2t) + (5)/(2)e^(4t) -2\\dy =[-(1)/(2) e^(-2t) + (5)/(2)e^(4t) -2]dt\\\int dy =\int [-(1)/(2) e^(-2t) + (5)/(2)e^(4t) -2]dt\\\int dy =\int -(1)/(2) e^(-2t) dt + \int (5)/(2)e^(4t) dt - \int 2 dt\\\int dy = -(1)/(2) \int e^(-2t) dt + (5)/(2) \int e^(4t) dt - 2 \int dt\\](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/x66xy654564du7ixswvioaypi872eh7dlx.png)
![y = -(1)/(2) * -(1)/(2) e^(-2t) + (5)/(2) * (1)/(4) e^(4t) - 2 t + C_2\\y(t) = (1)/(4) e^(-2t) + (5)/(8) e^(4t) - 2 t + C_2](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/6fu3nedjono034xdg3bhn0zd6008c18m3v.png)
Finding the constant of integration :
Given initial condition
![y(0)=1](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/u9m8s1tucsegczm7xziv7bnbou4zn1z781.png)
![1=y(0) = (1)/(4) e^(-2(0)) + (5)/(8) e^(4(0)) - 2 (0) + C_2\\1 = (1)/(4) (1) + (5)/(8) (1) - (0) + C_2\\1 = (7)/(8) + C_2\\(1)/(8)=C_2](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/to67kf5wxb9zotehvpzvnmem7bxdywwyrk.png)
So,
![y(t) = (1)/(4) e^(-2t) + (5)/(8) e^(4t) - 2 t + (1)/(8)](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/xkd6qb7xt5xsftsgwqntjbh33byhtpj35l.png)
Checking the solution
![y(t) = (1)/(4) e^(-2t) + (5)/(8) e^(4t) - 2 t + (1)/(8)](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/xkd6qb7xt5xsftsgwqntjbh33byhtpj35l.png)
This matches our initial conditions here
![y(0) = (1)/(4) e^(-2(0)) + (5)/(8) e^(4(0)) - 2 (0) + (1)/(8) = 1](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/o0cnkcuh216aqpnqzxm1kewmsxxeomrt3h.png)
Going back to the function, differentiate:
![y' = [(1)/(4) e^(-2t) + (5)/(8) e^(4t) - 2 t + (1)/(8)]'\\y' = [(1)/(4) e^(-2t)]' + [(5)/(8) e^(4t)]' - [2 t]' + [(1)/(8)]'\\y' = (1)/(4) [e^(-2t)]' + (5)/(8) [e^(4t)]' - 2 [t]' + [(1)/(8)]'](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/ddnrul7a9chqt44oacermsqgd0xwo39dj5.png)
Apply Exponential rule and chain rule, then power rule
![y' = (1)/(4) e^(-2t)[-2t]' + (5)/(8) e^(4t)[4t]' - 2 [t]' + [(1)/(8)]'\\y' = (1)/(4) e^(-2t)(-2) + (5)/(8) e^(4t)(4) - 2 (1) + (0)\\y' = -(1)/(2) e^(-2t) + (5)/(2) e^(4t) - 2](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/9wnqv68dztbj0zzd45y2ltftedu0hwe03e.png)
This matches our first order step and the initial conditions there.
![y'(0) = -(1)/(2) e^(-2(0)) + (5)/(2) e^(4(0)) - 2=0](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/cg25nok7u37vn943nmcdqv1wgqhms5sav6.png)
Going back to the function y', differentiate:
![y' = -(1)/(2) e^(-2t) + (5)/(2) e^(4t) - 2\\y'' = [-(1)/(2) e^(-2t) + (5)/(2) e^(4t) - 2]'\\y'' = [-(1)/(2) e^(-2t)]' + [(5)/(2) e^(4t)]' - [2]'\\y'' = -(1)/(2) [e^(-2t)]' + (5)/(2) [e^(4t)]' - [2]'](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/axu38tlxx2e1wjfivnop88758sn69z9y5d.png)
Applying the Exponential rule and chain rule, then power rule
![y'' = -(1)/(2) e^(-2t)[-2t]' + (5)/(2) e^(4t)[4t]' - [2]'\\y'' = -(1)/(2) e^(-2t)(-2) + (5)/(2) e^(4t)(4) - (0)\\y'' = e^(-2t) + 10 e^(4t)](https://img.qammunity.org/2023/formulas/advanced-placement-ap/high-school/qveq8luplw5xzgrae83z3ax00paabquf5w.png)
So our proposed solution is a solution to the differential equation, and satisfies the initial conditions given.